Odpowiedzi

2010-01-14T19:50:12+01:00
A) x + (y +x)= x+y+x=2x+y
b)3x kw + 3x kw +5 -7) = 6x²-2
c) (3x kw +3x + 5) + (2x kw + 2)= 5x²+3x+7
d) (3x kw + 4x + 8) - (x kw + 3x)=3x³+4x+8-x²-3x=2x²-x+8
e) (a + b) - (a + b)= a+b-a-b=0
2010-01-14T19:50:26+01:00
A)2x+y
b)6xkw -2
c)5xkw + 3x +7
d)2xkw + x +8
e)0
2010-01-14T19:52:59+01:00
A) x + (y+x)= 2x + y
b) 3x kw + 3x kw + 5 - 7= 6x kw - 2
c) (3x kw + 3x +5) + ( 2x kw+ 2) = 5x kw + 3x + 7
d) (3x kw + 4x + 8) - (x kw + 3x) = 2x kw + x + 8
e) (a+b) - (a-b) = 0